Looking beyond literacy and phonology: word learning and phonological cue use in children with and without dyslexia - van Viersen, Sietske; Kerkhoff, Annemarie; de Bree, Elise H. (Frontiers in Language Sciences, 2024)
This study investigated whether children with and without dyslexia differ in word learning and whether phonological cues to word class play a role. If children with dyslexia have difficulties with implicit learning, they might be less sensitive to such cues. A group of 92 Dutch primary school children from grades 3 to 6 participated in a word learning experiment, consisting of children with dyslexia (n = 46) and typically developing children (n = 46). Test items were four monosyllabic ‘verb-like’ nonwords (e.g., voek) and four bisyllabic ‘noun-like’ nonwords (e.g., banijn). They were presented as novel verbs or nouns in a two word sentence frame (e.g., “I voek” or “a voek”), paired with pictures of unfamiliar actions or objects. Nonwords were either consistent (e.g., “I voek”, “a banijn”) or inconsistent (e.g., “I banijn”, “a voek”) with word class. The word learning experiment consisted of a repetition, identification, and naming phase. Children with dyslexia showed lower word learning outcomes in the naming phase. However, phonological cues did not affect word learning in either group. Regression analyses indicated that phoneme awareness, receptive vocabulary, and nonword reading were predictors of word learning for all children. These findings indicate that Dutch children with dyslexia have more difficulty in recalling novel words, fitting in with their phonological difficulties. Phonological cues to word class did not contribute to word learning in either group.